Decision Support Systems - Jao, Chiang (IntechOpen, 2012)
Pacing through second decade of the 21th century, more computer users are widely adopting technology-based tools and information-enriched databases to focus on supporting managerial decision making, reducing preventable faults and improving outcome forecasting. The goal of decision support systems (DSS) is to develop and deploy information technology-based systems in supporting efficient practice in multidiscipline domains. This book aims to portray a pragmatic perspective of applying DSS in the 21th century. It covers diverse applications of DSS, primarily focusing on the resource management and outcome forecast. Our goal was to provide the broad understanding of DSS and illustrate their practical applications in a variety of fields related to real life.